Use of APAAP technique on paraffin wax embedded bone marrow trephines. - Erber, W N (1989)
The immunoalkaline phosphatase (APAAP) technique was applied to the labelling of decalcified sections of formalin fixed, paraffin wax embedded bone marrow trephine biopsy specimens. A panel of monoclonal antibodies reactive with haemopoietic and epithelial antigens, which survive routine formalin fixation, was assessed on 72 cases of haematological malignancy (including acute and chronic leukaemias and lymphomas) showing bone marrow infiltration. The APAAP method showed clear distinct labelling of antigen positive cells without loss of antigens due to decalcification. Both normal or reactive single cells present in the sample and neoplastic cell populations could be identified morphologically and their antigenic phenotype and cellular origin, whether lymphoid or myeloid, established. The application of the APAAP method to routinely prepared paraffin wax embedded trephines has many advantages over the assessment of specially prepared cryostat sections of bone marrow.